Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1515/sjpain-2018-0321
|View full text |Cite
|
Sign up to set email alerts
|

Taboo gesticulations as a response to pain

Abstract: Abstract Background and aims Prior research indicates that swearing increases pain tolerance and decreases pain perception in a cold pressor task. In two experiments, we extend this research by testing whether taboo hand gesticulations have a similar effect. Methods Study 1 focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…Our finding that taboo gestures can have a hypoalgesic effect differs from the conclusion of Jacobs et al (2018) who found that producing a taboo gesture did not affect pain in their study. There are several methodological differences that could account for the difference.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our finding that taboo gestures can have a hypoalgesic effect differs from the conclusion of Jacobs et al (2018) who found that producing a taboo gesture did not affect pain in their study. There are several methodological differences that could account for the difference.…”
Section: Discussioncontrasting
confidence: 99%
“…They found that, despite being rated as similarly humorous to the swear word (“fuck”), the made-up word did not reduce pain on the cold pressor task compared to a neutral word whereas the swear word did. Further, Jacobs et al (2018) found that the middle finger gesture was rated as more humorous than the neutral gesture, though the middle finger gesture did not actually relieve pain in their study. Taken together, these findings suggest that humor is probably not the most important component of a swear word or taboo act that leads it to reduce pain.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“… Hostetter and Rascon-Powell (2022) did not report effect sizes or conduct power analysis. However, Jacobs et al (2019) conducted two well-powered experiments to assess the pain modulating effect of the “middle finger” gesture. Their results showed no significant impact of taboo gestures on pain tolerance or pain perception ( Jacobs et al, 2019 ).…”
Section: Overview Of Swearing and Pain Modulationmentioning
confidence: 99%
“…However, Jacobs et al (2019) conducted two well-powered experiments to assess the pain modulating effect of the “middle finger” gesture. Their results showed no significant impact of taboo gestures on pain tolerance or pain perception ( Jacobs et al, 2019 ). These inconsistent findings may stem from variations in the experimental procedures.…”
Section: Overview Of Swearing and Pain Modulationmentioning
confidence: 99%